SUBGRUP FUZZY ATAS SUATU GRUP - Fatkhur Rozi; Ari Wardayani; Suroto Suroto (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2014)
This paper discusses a fuzzy subgroup of a classical group. It’s constructed by defining fuzzy subsets and employing products and inverse notions on classical group. The result obtained is sufficient and necessary conditions for the fuzzy subset to be fuzzy subgroup.